Triacylglycerol metabolism in isolated rat kidney cortex tubules - Wirthensohn, Gabriele (1980)
Triacylglycerol metabolism has been studied in kidney cortex tubules from starved rats, prepared by collagenase treatment. Triacylglycerol was determined by a newly developed fully enzymic method. Incubation of tubules in the absence of fatty acids led to a decrease of endogenous triacylglycerol by about 50% in 1h. Addition of albuminbound oleate or palmitate resulted in a steady increase of tissue triacylglycerol over 2h. The rate of triacylglycerol synthesis was linearly dependent on oleate concentration up to 0.8mm, reaching a saturation at higher concentrations. Triacylglycerol formation from palmitate was less than that from oleate. This difference was qualitatively the same when net synthesis was compared with incorporation of labelled fatty acids. Quantitatively, however, the difference was less with the incorporation technique. Gluconeogenic substrates, which by themselves had no effect on triacylglycerol concentrations, stimulated neutral lipid formation from fatty acids. Glucose and lysine did not have such a stimulatory effect. Inhibition of gluconeogenesis from lactate by mercaptopicolinic acid likewise inhibited triacylglycerol formation. This inhibitory effect was seen with oleate as well as with oleate plus lactate. When [2-(14)C]lactate was used the incorporation of label into triacylglycerol was found in the glycerol moiety exclusively. Addition of dl-β-hydroxybutyrate (5mm) to the incubation medium in the presence of oleate or oleate plus lactate led to a significant increase in triacylglycerol formation. In contrast with the gluconeogenic substrates, dl-β-hydroxybutyrate had no stimulatory effect on fatty acid uptake. The results suggest that renal triacylglycerol formation is a quantitatively important metabolic process. The finding that gluconeogenic substrates, but not glucose, increase lipid formation, indicates that the glycerol moiety is formed by glyceroneogenesis in the proximal tubules. The effect of ketone bodies seems to be caused by the sparing action of these substrates on fatty acid oxidation. The decrease of triacylglycerol in the absence of exogenous substrates confirms previous conclusions that endogenous lipids provide fatty acids for renal energy metabolism.